Betti numbers of edge ideals of some split graphs. Issue 12 (1st December 2020) - Singh, Pavinder; Verma, Rohit
Abstract: In this article, we shall compute the graded Betti numbers of edge ideals of complete split and nearly complete split graphs. Also, we obtain the bounds on the Betti numbers and the projective dimension of edge ideals of split graphs.